SIGNATURES OF LARGE-SCALE STRUCTURE OF UNIVERSE IN X-RAYS - Tugay, A. V. (Одеські астрономічні публікації, 2012)
A new sample of 4299 galaxies with X-ray emission was obtained in this work by cross-correlating 2XMM catalog of X-ray sources with HyperLeda database of galaxies. We analyzed distributions of optical and X-ray fluxes, redshifts and X-ray luminosities for this sample. Virgo and Coma galaxy clusters can be easily detected at redshift-space distribution of X-ray galaxies. X-ray luminosity function of our galaxies shows the evidences of cosmological evolution, even at low redshifts.